Effects of Prior Knowledge and Lesson Outline on Note Taking and Test Scores - Olmos, Oscar L.; Lusung-Oyzon, Maria Vanessa P. (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol. 66, No. 1 (December 2008), 2010)
This study sought to find the effects of two teaching strategies—the use of lesson outline and the activation of prior knowledge—on note taking and test scores. The relationship between notes and test scores was also determined. Three intact classes of freshmen high school boys were assigned to three note taking environments prior to attending a videotaped lecture class. They were randomly assigned to prior knowledge environment, lesson outline environment, and the control environment. A posttest was administered immediately after the lecture and the students’ notes were collected and rated. The same test was administered to the students a week later, after they have reviewed their notes. Results indicated that prior knowledge and lesson outline do not necessarily induce any specific note taking strategy. Note taking and review of notes are related to better test scores. Correlation tests showed that high test scores are associated with more notes.